Sustainable Approach of Functional Biomaterials-Tissue Engineering for Skin Burn Treatment: A Comprehensive Review - Loai A. Elfawy; Chiew Yong Ng; Ibrahim N. Amirrah; Zawani Mazlan; Adzim Poh Yuen Wen; Nur Izzah Md Fadilah; Manira Maarof; Yogeswaran Lokanathan; Mh Busra Fauzi (MDPI AG, 2023)
Burns are a widespread global public health traumatic injury affecting many people worldwide. Non-fatal burn injuries are a leading cause of morbidity, resulting in prolonged hospitalization, disfigurement, and disability, often with resulting stigma and rejection. The treatment of burns is aimed at controlling pain, removing dead tissue, preventing infection, reducing scarring risk, and tissue regeneration. Traditional burn wound treatment methods include the use of synthetic materials such as petroleum-based ointments and plastic films. However, these materials can be associated with negative environmental impacts and may not be biocompatible with the human body. Tissue engineering has emerged as a promising approach to treating burns, and sustainable biomaterials have been developed as an alternative treatment option. Green biomaterials such as collagen, cellulose, chitosan, and others are biocompatible, biodegradable, environment-friendly, and cost-effective, which reduces the environmental impact of their production and disposal. They are effective in promoting wound healing and reducing the risk of infection and have other benefits such as reducing inflammation and promoting angiogenesis. This comprehensive review focuses on the use of multifunctional green biomaterials that have the potential to revolutionize the way we treat skin burns, promoting faster and more efficient healing while minimizing scarring and tissue damage.